1989
DOI: 10.1159/000195739
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Aminophylline and Salbutamol to Improve Respiratory Muscle Function and Exercise Tolerance in Healthy Humans

Abstract: We investigated the effects of intravenously administered aminophylline (A; 6 mg/kg over 20 min, followed by 0.9 mg/kg/h), salbutamol (S; 4 µg/kg over 20 min, followed by 3 µg/kg/h) and placebo (P; saline solution) on the strength of the respiratory muscles, the ventilatory endurance and the exercise tolerance in 7 healthy humans. Neither A nor S caused bronchodilatation, as shown by the lack of change in FEV1. The strength of respiratory muscles, as measured by maximal inspiratory pressure (MIP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 12 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…This result is in keeping with previous reports (McKenzie et al 1983;Violante et al 1989;Malerba et al 1996;Carlsen et al 1997), and conWrmed in the present study with the highest possible tolerated dose given intravenously. It thus appears that 2 agonist-induced increases in stroke volume, indirectly suggested by increased pulse pressures and O 2 pulse in the present experiments, related to positive inotropic eVects and increased venous return (Hopkins et al 1996), cannot contribute to an improved aerobic exercise capacity through and increased O 2 delivery to the exercising muscles.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in keeping with previous reports (McKenzie et al 1983;Violante et al 1989;Malerba et al 1996;Carlsen et al 1997), and conWrmed in the present study with the highest possible tolerated dose given intravenously. It thus appears that 2 agonist-induced increases in stroke volume, indirectly suggested by increased pulse pressures and O 2 pulse in the present experiments, related to positive inotropic eVects and increased venous return (Hopkins et al 1996), cannot contribute to an improved aerobic exercise capacity through and increased O 2 delivery to the exercising muscles.…”
Section: Discussionsupporting
confidence: 94%
“…Muscle strength was evaluated by somewhat differing methods. In an investigation of muscle metabolism, there was an increase in forearm muscular endurance that was considered due to a delayed onset of intracellular metabolic acidosis 27 . But this is an interesting finding and may account for the delayed onset of ischaemic arm pain found by Jonzon, given a meta‐analysis of pain perception showed that a wide spectrum of sportspeople have higher pain thresholds than the normally active controls 33 .…”
Section: Discussionmentioning
confidence: 99%
“…aminophylline and salbutamol at therapeutic concentrations have no clinically relevant beneficial effects on ventilatory muscle function and exercise tolerance in healthy subjects 27 …”
Section: Theophylline Aerobic Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…These results, despite being somewhat inconsistent due to the lack of studies, agree with other studies already performed. 4,5 Regarding inhaled β2-agonists' effect on endurance TTE, no significant effect was shown. However, when considering the oral route, the effect was statistically significant for salbutamol, which explains the prohibition of this route of administration for athletes granted a TUE.…”
Section: F I G U R E 2 Forest Plot Representing the Comparison Of Md Of Endurance Time To Exhaustion (Tte) Between β2-agonists And Placebmentioning
confidence: 90%